2017
DOI: 10.1111/jcmm.13172
|View full text |Cite
|
Sign up to set email alerts
|

ClassIIIantiarrhythmic drugs amiodarone and dronedarone impairKIR2.1 backward trafficking

Abstract: Drug‐induced ion channel trafficking disturbance can cause cardiac arrhythmias. The subcellular level at which drugs interfere in trafficking pathways is largely unknown. KIR2.1 inward rectifier channels, largely responsible for the cardiac inward rectifier current (IK 1), are degraded in lysosomes. Amiodarone and dronedarone are class III antiarrhythmics. Chronic use of amiodarone, and to a lesser extent dronedarone, causes serious adverse effects to several organs and tissue types, including the heart. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Recordings were performed 24 h after transfection. In western blot experiments, HEK293T cells were grown on 60 mm tissue culture dishes and transfected using linear PEI as described earlier (Ji et al, 2017a). In immunofluorescence microscopy experiments, COS-7 cells were grown on Ø 15 mm coverslips, pre-coated with poly-L-lysine (Sigma-Aldrich), and transfected with K IR 2.1 (WT or ΔPEST) using Lipofectamine according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recordings were performed 24 h after transfection. In western blot experiments, HEK293T cells were grown on 60 mm tissue culture dishes and transfected using linear PEI as described earlier (Ji et al, 2017a). In immunofluorescence microscopy experiments, COS-7 cells were grown on Ø 15 mm coverslips, pre-coated with poly-L-lysine (Sigma-Aldrich), and transfected with K IR 2.1 (WT or ΔPEST) using Lipofectamine according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…COS-7 cells were stained essentially as described earlier (Ji et al, 2017a). Antibodies used were K IR 2.1 (1:250; Santa Cruz Biotechnology, Heidelberg, Germany, cat.…”
Section: Methodsmentioning
confidence: 99%
“…Class III antiarrhythmic drug amiodarone inhibits mTORC1 leading to stimulation of the autophagy pathway, which was explored in vitro (Balgi et al, 2009 ). In another in vitro study, we indicated lysosomal impairment by amiodarone and its synthetic analog dronedarone, which resulted in increased inward rectifier potassium channel K ir 2.1 expression and intracellular accumulation (Ji et al, 2017a ). The well-known drawback of amiodarone is its high incidence of side effects, including thyroid toxicity, pulmonary toxicity, hepatic toxicity, neurological toxicity, which seem to be related to the lifetime cumulative dose of the drug (Santangeli et al, 2012 ).…”
Section: Antiarrhythmic Drugs Affect Autophagy Pathwaysmentioning
confidence: 97%
“…I Kir is instead dictated by the electrochemical gradient and an increasing intracellular blocking of the pore when the membrane potential (E m ) > E K , resulting in an inward I K when E m < E K and an outward I K when E m > E k , which is progressively blocked as E m rises [ 197 ]. K ir channels are therefore important for maintenance of the hyperpolarised resting membrane potential and regulating activity in excitable cells, such as vascular smooth muscle [ 198 ], central neurons [ 199 ] and cardiomyocytes [ 200 ]. Subfamilies of K ir channels exist that are ATP-sensitive (K ATP channels; K ir 6. x ) and G-protein gated (G-protein inwardly rectifying K + channels- GIRKs; K ir 3. x ) [ 201 , 202 ].…”
Section: K + Channelsmentioning
confidence: 99%